The Presence Of Staphylococcus Aureus on The Skin, Nose, and Ear of Adolescent Footballers Before and After Training - William, John Laurence (2005)
The objective of the study was to determine the number of adolescent footballers carrying Staphylococcus aureus during outdoor and indoor training. One hundred twenty healthy male subjects age from 13 to 15 participated in the study. The subjects were assigned into two different training venues; outdoors and indoors. Swabs were taken before and after training at three sites of the body; skin, ear and nose. The strains were incubated in Baird Parker agar plates at 37OC. There was no significant difference for the numbers of S. aureus strains carriers between pre and post result for the skin, nose, and ear for outdoor training.Results for the number of S. aureus strains carriers on the skin, and nose between pre and post indoor training showed significant difference (p<0.05), however no significant difference was observed for the results on the ear. Number of carriers on the skin, ear, and nose for pre training was 60 (loo%), 56 (93%) and 56 (93%)) respectively, whereas for post training on the same sites were 44 (73%), 56 (93%), and 60 (loo%), respectively. As fur the estimated mean plate count of S. aureus strains, there was significant difference between the pre and post results on the ear and nose of Malays during outdoor training (~~0.05a)n d no significant difference for the estimated mean plate count of strain on the skin. The estimated mean plate count of S. aureus strain for Malays from the skin, ear and nose before training were 138*103, 190k 147 and 395k83, respectively and after training were 97*77, 71S4 and 498k75, respectively. For Indians, there was no significant difference for the plate count of S. aureus strain on the skin, ear, and nose between the pre and post results during outdoor training. As for indoor training, both Malays and Indians showed a significant difference between the pre and post results (p<0.05). The estimated mean plate count of strain during indoor training for Malays from the skin, ear and nose before training was 33*17, 71e8 and 312f55, respectively and 21k16, 44e6 and 452k89, respectively after training. For Indians, the estimated mean plate count of strain on the skin, ear, and nose before training was 72&1, 80Q1 and 309~104re spectively and 55*19,20062, and 466f1 09 respectively after training. In conclusion, the adolescent footballers are carriers during training either indoor or outdoor. Representative strains from the skin of adolescent footballers and environment were selected randomly for antibiotic resistance, plasmid, coagulase, and RAPD-PCR analysis. For the antibiotic resistance test, nineteen antibiotics were tested. Antibiotic resistance patterns with the strains tested from footbalfers training indoor, outdoor and environment were diverse. However, norfioxacine (0%), rifampicin (0%), imipenem (O%), methicillin (0%) and trirnethoprim-sulfamethoxazole (1 00%) showed a similar resistance patterns with the strains tested from footballers and the environment. Strains from the adolescent footballers training indoors and indoor environment have a higher Multiple Antibiotic Resistance (MAR) index compared from the strains from outdoor adolescent footballers and outdoor environment. The plasmid profiles of S. aureus strains isolated from the skin of footballers and the environment ranged between 1.8 to 3.4 megaDalton (mDa). The results of the plasmid profiles and antibiotic resistance showed that there was no correlation between plasmid carriage and resistance to a particular antibiotic tested. Thir4y-two S. aureus strains isolated from outdoors and indoors were found to be carrying coagulase genes of different sizes. Two strains produced three amplified coagulase gene fragments while one strain produ~ed two amplified coagulase gene fragments. The rest of the strains produced only one amplified coagulase gene fragment. As for the strains from the environment, Wo strains produced two amplified coagulase gene fragments and seven produced only one arnplifed coagulase gene fragment. The profiles obtained from RAPD contained 1 to 9 bands within the molecular size of 0.3 kbp to 5.0 kbp. From the dendrogram, the strains were divided into 2 major clusters and at 100% similarity there were four groups of strains. It can be concluded that the strains isolated from the footballers and environment were pathogenic due to the present of the coagulase gene.